Neratinib shows efficacy in the treatment of HER2 amplified carcinosarcoma in vitro and in vivo - Schwab, Carlton L. (Gynecol Oncol, 2015)
OBJECTIVE: Carcinosarcoma is a deadly gynecologic malignancy with few effective treatment options. The study of new therapies is difficult because of its rarity. The objective of this study was to determine the efficacy of neratinib in the treatment of HER2 amplified carcinosarcoma. METHODS: The efficacy of neratinib in the treatment of HER2 amplified carcinosarcoma was determined in vitro using seven primary carcinosarcoma cell lines with differential expression of HER2/neu. Data regarding IC(50), cell cycle distribution, and cell signaling changes were assessed by flow cytometry. The efficacy of neratinib was determined in treating mice harboring HER2 amplified carcinosarcoma xenografts. RESULTS: Two of seven (28.5%) carcinosarcoma cell lines were HER2/neu amplified. HER2/neu amplified cell lines SARARK6 and SARARK9 were significantly more sensitive to neratinib than the five non-HER2/neu amplified carcinosarcoma cell lines (mean±SEM IC(50): 0.014μM±0.004 vs. 0.164μM±0.019 p=0.0003). Neratinib treatment caused a significant build up in G0/G1 phase of the cell cycle, arrest auto phosphorylation of HER2/neu and activation of S6. Neratinib inhibited tumor growth (p=0.012) and prolonged survival in mice harboring HER2 amplified carcinosarcoma xenografts (p=0.0039). CONCLUSIONS: Neratinib inhibits HER2 amplified carcinosarcoma proliferation, signaling, cell cycle progression and tumor growth in vitro. Neratinib inhibits HER2/neu amplified xenograft growth and improves overall survival. Clinical trials are warranted.